2022
DOI: 10.3390/molecules27072057
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Cathinones: Recent Developments, Enantioselectivity Studies and Enantioseparation Methods

Abstract: New psychoactive substances represent a public health threat since they are not controlled by international conventions, are easily accessible online and are sold as a legal alternative to illicit drugs. Among them, synthetic cathinones are widely abused due to their stimulant and hallucinogenic effects. To circumvent the law, new derivatives are clandestinely synthesized and, therefore, synthetic cathinones keep emerging on the drug market, with their chemical and toxicological properties still unknown. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 118 publications
(193 reference statements)
0
17
0
Order By: Relevance
“…1 H, 13 C, 19 F NMR spectra, and all 2D experiments were carried out using Varian Gemini 400 Hz DDR2 and JEOL-ECZL400G with deuterated solvents (chloroform and methanol). Every sample was measured at 25 C. Deuterated solvents were purchased from Chemstar (Plze ň, Czech Republic).…”
Section: Nmr and Ms Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…1 H, 13 C, 19 F NMR spectra, and all 2D experiments were carried out using Varian Gemini 400 Hz DDR2 and JEOL-ECZL400G with deuterated solvents (chloroform and methanol). Every sample was measured at 25 C. Deuterated solvents were purchased from Chemstar (Plze ň, Czech Republic).…”
Section: Nmr and Ms Analysesmentioning
confidence: 99%
“…During intoxication, a wide range of adverse side effects has been observed, ranging from cardiovascular and neurological to psychiatric effects, such as arterial hypertension, tachycardia, hallucinations, agitation, hyperthermia, and changes in locomotor behavior 9–12 . Due to the chiral center in their structure, cathinones can occur in two enantiomers, with one enantiomer typically exhibiting a greater psychological effect on the human biological system than the other 13,14 . For instance, studies demonstrated that ( S )‐methcathinone possesses a stronger stimulation effect than ( R )‐methcathinone 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For meanwhile established illicit drugs such as mephedrone, and also some newer cathinone derivatives, several studies have been conducted in this regard. 6,7 For mephedrone, it was shown that the enantiomers differ substantially in their neuropharmacological profiles. While for the S-enantiomer higher serotonergic effects were shown, the R-enantiomer displays a much higher preference for the dopaminergic system.…”
mentioning
confidence: 99%
“…Furthermore, chiral methods can also be beneficial in semipreparative scale to collect pure enantiomers for further studies, as is already shown in literature for various synthetic cathinones. 7,10,[14][15][16][17] To date, a wide range of different methods for enantioseparation of synthetic cathinones and other NPS exists in gas chromatography (GC), [18][19][20][21] capillary electrophoresis (CE), [21][22][23][24] supercritical fluid chromatography (SFC), 25,26 and high-performance liquid chromatography (HPLC). 6,7,10,19,20,[26][27][28][29][30][31][32] During the last years, various chiral stationary phases (CSPs) have been tested by our working group on the basis of different substance classes of NPS, bought in internet head shops or seized by Austrian Police.…”
mentioning
confidence: 99%